1996
DOI: 10.1002/aheh.19960240606
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Selected Compounds on Thermocyclops oblongatus, one of the Main Intermediate Hosts of Guinea Worm in Africa

Abstract: In Heft 1/97 der Acta hydrochimica et hydrobiologica sind folgende BeitrBge erschienen: Terbuthylazine and Deethylterbuthylazinc, in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The influence of time in short-term bioassays was considered in five studies, where sensitivity to pesticides was shown to increase with time of exposure (Ludemann and Neumann 1960;Robertson and Bunting 1976;Notenboom et al 1992;Willis 1999;Kulkarni et al 2013a). Acute sensitivity to the insecticide Temephos has been investigated in three different studies up to now (Table 2): besides differences in the experimental conditions, data indicated that the cyclopoid Macrocyclops albidus and Thermocyclops oblongatus are more sensitive than Thermocyclops hyalinus at 24 h of exposure (Samman and Thomas 1978;Chippaux et al 1996;Marten et al 1993). Notenboom et al (1992) and Willis (1999) tested the effect of Pentachlorophenol, respectively, on the hypogean species Parastenocaris germanica and on three surface freshwater species, namely, the calanoid Boeckella delicata and Calamoecia lucasi and the cyclopoid Mesocyclops leuckarti.…”
Section: Review Of Literature Datamentioning
confidence: 99%
“…The influence of time in short-term bioassays was considered in five studies, where sensitivity to pesticides was shown to increase with time of exposure (Ludemann and Neumann 1960;Robertson and Bunting 1976;Notenboom et al 1992;Willis 1999;Kulkarni et al 2013a). Acute sensitivity to the insecticide Temephos has been investigated in three different studies up to now (Table 2): besides differences in the experimental conditions, data indicated that the cyclopoid Macrocyclops albidus and Thermocyclops oblongatus are more sensitive than Thermocyclops hyalinus at 24 h of exposure (Samman and Thomas 1978;Chippaux et al 1996;Marten et al 1993). Notenboom et al (1992) and Willis (1999) tested the effect of Pentachlorophenol, respectively, on the hypogean species Parastenocaris germanica and on three surface freshwater species, namely, the calanoid Boeckella delicata and Calamoecia lucasi and the cyclopoid Mesocyclops leuckarti.…”
Section: Review Of Literature Datamentioning
confidence: 99%
“…For instance, the 24h LC 50 of PCMX to the rotifer Brachionus koreanus was reported to be 24.264 (20.892-28.243) (Won et al 2022), 31.8 (26.5-36.8 mg/l) for the nematode Caenorhabditis elegans (Sreevidya et al 2018), 48.6 (45.8-52.0) for the mite Dermatophagoides pteronyssinus and 60.9 (46.7-89.1) for the mite Dermatophagoides farina(Suhaili et al 2016). However, the sensitivity of O. alluaudi to PCMX was lower than what was reported for a crustacean, Thermocyclops oblongatus, which had a 24h LC 50 of 0.17 mg/l(Chippaux et al 1996). There is a paucity of information on the acute effect of PCMX on invertebrates exposed for more than 24 hours, but the 48 hour LC 50 for Daphnia magna was reported to be 8.78 mg/l (Novak et al 2021).…”
mentioning
confidence: 95%